Distribution of macrophages in the developing cochlea of the common marmoset, a primate model animal - Hosoya, Makoto; Kitama, Tsubasa; Shimanuki, Marie N.; Nishiyama, Takanori; Oishi, Naoki; Okano, Hideyuki; Ozawa, Hiroyuki (Frontiers in Immunology, 2023)
Macrophages are essential immune cells in the cochlea that contribute to inflammation, tissue repair, and homeostasis. They also play an important role in local cochlear immunity. The developmental immigration and maturation of macrophages in the cochlea have been investigated and are considered essential for normal hearing acquisition. Most of our current knowledge regarding cochlear development is based on rodent models because of the ethical challenges of using human fetal samples for research. However, inter-species differences between rodents and humans have been reported. In this study, we used a primate animal model to investigate the distributions of macrophages in the developing cochlea. The common marmoset (Callithrix jacchus), a small monkey species that inhabits the New World, was used as the model. Methods: We investigated the distribution of macrophages in the developing cochlea of the common marmoset by performing immunohistochemical analyses of cochlear tissue from common marmoset embryos at different development stages. Results: We revealed detailed distribution changes in the macrophages of a primate animal model cochlea. This observation indicates that most of the changes in the general distribution of macrophages were well preserved between rodents and this primate. The distribution changes observed in the common marmoset were also compatible with observations in the human fetus; although, observations in the human fetus are limited. Our observations in this study also revealed several differences between common marmosets and rodents.The time course of immunological development and maturations established in this study will aid in the study of the primate-specific developmental biology of the inner ear. These observations may eventually lead to new therapeutic strategies for hearing loss in humans. In addition, understanding the immunological steady-state of the cochlea may help in the study of ageand genetic-induced hearing loss and in the design of regenerative therapies.